Convergence of natural p-means for the p-Laplacian in the Heisenberg group. (October 2022) - Domokos, András; Manfredi, Juan J.; Ricciotti, Diego; Stroffolini, Bianca
Abstract: In this paper we prove uniform convergence of approximations to p -harmonic functions by using natural p -mean operators on bounded domains of the Heisenberg group H which satisfy an intrinsic exterior corkscrew condition. These domains include Euclidean C 1, 1 domains.